2016
DOI: 10.1007/s13181-016-0559-3
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Recommended Naloxone Dosing for Opioid Overdose by Medical Specialty

Abstract: There are variations in the recommended doses for naloxone with ranges spanning an order of magnitude. Further exploration is needed to determine the dose that balances reversal of respiratory depression with mitigation of withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…While our administered dose of naloxone (0.4mg/70kg initial and 0.8mg/70kg secondary if necessary) was lower than the 10mg/70kg dose used by Compton et al, (2004) and in our pilot study (Chu et al, 2009) we observed statistically significant subjective and objective signs of OW suggesting our selected doses were effective. Interestingly, there is currently no universally agreed upon dose of naloxone for use in rescue situations suggesting that little is known concerning individual variation in response to naloxone dosing (Connors & Nelson, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…While our administered dose of naloxone (0.4mg/70kg initial and 0.8mg/70kg secondary if necessary) was lower than the 10mg/70kg dose used by Compton et al, (2004) and in our pilot study (Chu et al, 2009) we observed statistically significant subjective and objective signs of OW suggesting our selected doses were effective. Interestingly, there is currently no universally agreed upon dose of naloxone for use in rescue situations suggesting that little is known concerning individual variation in response to naloxone dosing (Connors & Nelson, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Rationale. Naloxone rescue should be initiated at a dose less than or equal to 0.05 mg intravenous or intramuscular over 1 minute and repeated frequently based on institutional protocol and patient response until sedation and respiratory issues resolve (Connors & Nelson, 2016). The panel recommends that when naloxone reversal is required, clinicians consider the duration of action of naloxone and the duration of action of the opioid and implement frequent monitoring of the patient for any ongoing signs of OIUAS and OIRD.…”
Section: Recommendation 11mentioning
confidence: 99%
“…Within the medical literature there is wide variation in naloxone dosing recommendations . Connors et al . examined a convenience sample of 25 sources.…”
Section: Introductionmentioning
confidence: 99%
“…Of these references, 12 (48%) suggested starting doses <50 μg while nine (36%) recommended dosages 10 times higher. More conservative dosing protocols dominated recent toxicology specific publications …”
Section: Introductionmentioning
confidence: 99%